Effect of kangaroo mother care in low-birth-weight babies in reference to breastfeeding in NICU at a tertiary care centre - An observational study - Dulal Kalita; Sumana Sarma (Asian Journal of Medical Sciences)
Background: Kangaroo mother care (KMC) is described by the WHO as early, ongoing, and prolonged skin-to-skin contact between a mother and her preterm infants.